SOSIALISASI DAMPAK PERGAULAN BEBAS PADA REMAJA DI JEMAAT GKLB EBEN HAEZER ETENG KECAMATAN LAMALA KABUPATEN BANGGAI - Poyungi, Yurike Suhertian; Unsong, Imelda Frida; Kezia Maranata Harjono; Lin Margareta; Felix Lamato (Jurnal Abdi Masyarakat Multidisiplin, 2024)
Promiscuity is a form of deviant behavior that crosses the boundaries of existing social and recligious norms. Teenagers are usually the main targets of this deviation. This service activity aims to gain knowledge about the very detrimental impacts of promiscuity and increase awaraness to be involved in efforts to prevent promiscuity for young people. Therefore, AMIK Luwuk Banggai, which consists of a team of lectures and students, collaborated to carry out this service at Jemaat GKLB Eben Haezer in Eteng Village, Lamala Distric, Banggai Regency.